Isolation and phylogenetic analysis of SARS-CoV-2 variants collected in Russia during the COVID-19 outbreak. (October 2020) - Kozlovskaya, Liubov; Piniaeva, Anastasia; Ignatyev, Georgy; Selivanov, Alexey; Shishova, Anna; Kovpak, Anastasia; Gordeychuk, Ilya; Ivin, Yury; Berestovskaya, Anastasia; Prokhortchouk, Egor; Protsenko, Denis; Rychev, Mikhail; et al.
Highlights: There were multiple importations and several patterns of spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Russia. There are no signs of direct virus importations from China. SARS-CoV-2 variants circulating in Russia mostly contain seven common mutations. Abstract: Objectives: The outbreak of coronavirus disease 2019 (COVID-19) started in December 2019 in China and then spread worldwide over the following months, involving 188 countries. The objective of this study was to determine the molecular epidemiology of the COVID-19 outbreak in Russia. Methods: In this study, two severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strains were isolated and genetically characterized. A phylogenetic analysis of all available Russian sequences was then performed and these were compared to the epidemiological data on COVID-19 incidence to evaluate the molecular epidemiology and pattern of virus spread in the territory of Russia. Results and conclusions: Whole genome analysis of the isolates obtained in this study and 216 others isolated in Russia revealed a set of seven common mutations when compared to the original Wuhan virus, including amino acid substitutions in spike protein S and nucleoprotein N, possibly affecting their properties. Phylogenetic analysis of all Russian sequences and 8717 sequences from other countries showed multiple importations of the virus into Russia, local circulation, and several patterns of virus spread.